Introduction to the Special Issue: Career Development and Intervention in Chinese Contexts. Issue 3 (September 2016) - Fan, Weiqiao; Leong, Frederick T. L.
Abstract : Career development and career intervention have been affected by globalization in culture, politics, and economics. Career development among Chinese people, especially youth, shows particular characteristics with the influences of Chinese cultural features such as collectivistic values. The authors review the challenges of career development and intervention in different types of Chinese societies, including a shortage of indigenous theoretical models and assessment instruments; a lack of professional training and education for researchers, practitioners, educators, and counselors; and less positive attitudes toward career counseling and education. The authors then overview the content of this special issue, focusing on career development and intervention of Chinese people living in Shanghai, Taiwan, Hong Kong, Macau, the United States, Canada, and Singapore. The articles address specific challenges, barriers, and features of career intervention, education, and development in these Chinese societies. Approaches and strategies for improving career development and intervention in these different contexts are discussed.